2010
DOI: 10.1177/0363546509353133
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Anteromedial and Posterolateral Bundles of the Anterior Cruciate Ligament on External and Internal Tibiofemoral Rotation

Abstract: Noninvasive measurement of tibiofemoral rotation might be useful to detect anterior cruciate ligament tears and to evaluate the restoration of rotational stability after anterior cruciate ligament surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 40 publications
(48 reference statements)
3
38
0
1
Order By: Relevance
“…Early in vivo studies demonstrated a similar increase of rotation in the injured knee by 10 % (3°) compared to the healthy knee [72]. More specifically, the posterolateral bundle may play a specific role in restraining rotation as its section induced the major increase (3°at 5 Nm) in internal rotation [73]. To date, only the sensitivity and specificity of the Rotameter to detect an ACL injury has been reported in the literature [67•].…”
Section: Knee Laxity In the Injured Knee Diagnosis Of Acl Injuriesmentioning
confidence: 99%
“…Early in vivo studies demonstrated a similar increase of rotation in the injured knee by 10 % (3°) compared to the healthy knee [72]. More specifically, the posterolateral bundle may play a specific role in restraining rotation as its section induced the major increase (3°at 5 Nm) in internal rotation [73]. To date, only the sensitivity and specificity of the Rotameter to detect an ACL injury has been reported in the literature [67•].…”
Section: Knee Laxity In the Injured Knee Diagnosis Of Acl Injuriesmentioning
confidence: 99%
“…Studies addressing function of the two bands also conflict. Bach and Hull (1998) found no difference in band strain on internal rotation, whereas Lorbach et al (2010) found that transection of the posterolateral band increased internal rotation on rotational torque at 30° flexion, and was not significantly increased by transecting the anteromedial band.…”
Section: Internal Rotationmentioning
confidence: 96%
“…The position of the femoral attachment of the ACL is more important for the kinematics after the ACL reconstruction [1,2]. The position of the femoral foot-print is well known [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The goals of this study were: (1) To evaluate the knee IR stability after the singlebundle ACL reconstruction accompanied by the ALL reconstruction and to compare it with the doublebundle ACL technique. (2) To analyse when the ALL is necessary to reconstruct.…”
mentioning
confidence: 99%